Płaskie osiowo-symetryczne zadanie teorii sprężystości w ośrodku dyskretnym - J. Śliżewicz (Engineering Transactions, 1969)
This paper is based on the theory of a discrete medium introduced by H. Frackiewicz. For a plane axially-symmetrical grid possessing rigidity of stretching and bending, and loaded with an axial symmetry, the displacement equations are introduced, consisting of a set of three linear difference equations of the second order. These equations are solved for preassumed rigidities. For a concrete case the displacements and state of stresses are found, determining the arbitrary constants from the boundary conditions.